Preventing Mpox Importation: Strengthening Public Health Surveillance in Pakistan (Journal of Fatima Jinnah Medical University, 2024)
Pakistan, a total of eight Mpox cases have been reported in 2024 with the most recent case reported on 20 December.13 So far Pakistan has imported 17 Mpox cases (nine in 2023 and eight in 2024) from the Kingdom of Saudi Arabia and UAE, with one mortality. The sequencing of Mpox samples by the National Institute of Health, Islamabad detected less severe Clade IIb and lineage A.2.1 in all cases.12          Thus far, no case of human-to-human local transmission has been detected from Pakistan. However, in the absence of effective border screening programs, lack of surveillance, non-existent nationwide diagnostic facilities, a shortage of trained workforce, a weak case reporting system, and stigma associated with the disease, it cannot be confidently claimed that no Mpox cases exist in the country. Moreover, the presence of asymptomatic cases and similarities with other diseases further make detection of the cases challenging.          The global cases are declining over time due to increased awareness and vaccination efforts, localized outbreaks, asymptomatic transmission, and limited surveillance remain critical barriers to eradication. Therefore, there is a need to strengthen public health surveillance, diagnostic services, trained manpower, and public health systems to prevent future outbreaks. A collective response from international and national bodies is required to stop the spread of the disease and to reduce associated morbidity and mortality.